AN ANALYSIS OF AAVE GRAMMATICAL FEATURES AS DEPICTED IN THE UTTERANCES OF CHRISTOPHER WALLACE IN “NOTORIOUS” MOVIE - PRASETYO, YUDI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: African American Vernacular English, Christopher Wallace in Notorious Movie. Language is very important for human. It is functioned as a tool for people to communicate with others, to deliver ideas, messages, feeling, etc. Language and society are closely related. Certain society speaks certain language or certain language shows identities of certain society. African Americans speak different kind of English called African American Vernacular English (AAVE) which has distinctive grammatical features compared to standard English. The researcher conducts a research about AAVE grammatical features that are used by Christopher Wallace in Notorious Movie using theories by Rickford and Wolfram. This research focuses on two problems: (1) What utterances are containing AAVE grammatical features found in Christopher Wallace’s utterances in the movie entitled Notorious?, (2) What AAVE grammatical features are performed by Christopher Wallace in the movie entitled Notorious?.This research uses qualitative approach in document analysis to describe the AAVE grammatical features used by Christopher Wallace in Notorious Movie. The data are transcribed utterances produced by Christopher Wallace taken from Notorious Movie which is downloaded from ganool.com website.This research reveals that most of AAVE grammatical features are found in the utterances of Christopher Wallace in Notorious Movie namely ain’t as a general preverbal negator, multiple negations, formation of direct question, absence of relative pronoun, absence of third person singular present tense –s, absence of auxiliary, generalization of was to use with plural subject, use of been to mark a state or action that began a long time ago and is still relevant, use of existential they got as a plural equivalent of singular it is, use of done to emphasize the completed nature of an action, use of auxiliary verb don’t instead of doesn’t, use of negative inversion, and use of y’all and they to mark second person plural and third person plural posessive.The researcher hopes that this research can contribute a better and deeper understanding about African American Vernacular English. He suggests the nextresearchers especially English Department students conduct the research with different objects and theories of AAVE since this research does not cover all aspects of language function.